Ecological Metaphor in Shinkai Makoto’s Animated Film Tenki No Ko - Sutanto, Marisa Rianti; Indrabhaswara, Kemal Yusuf; Sutandio, Anton (Humanus, 2023)
This paper discusses a 2019 animated film entitled Tenki no Ko by Shinkai Makoto. This film is Shinkai’s most commercially successful work. Like other Shinkai’s works, Tenki no Ko talks about a romantic story between two teenage characters. The film is not only a work of fantasy or romance, but it also brings up natural elements that are expressed in the plot. Not only do the natural elements expressed in the film send the message of global warming, but they also show the reality of human life. Therefore, the analysis will be carried out with an epistemological method to prove the truth of the reality of life that the film expresses. The explanatory element applied to the object is a metaphorical expression of the scenes with reference to the multimodal metaphor theory through an ecological perspective. The analysis aims to trace ecological metaphorical expressions in the film. The findings show that the dominant metaphorical expression is “human life is like the weather” which can be called an ecological metaphor in connection with the ecological relationship between the human characters and their environment.